Relationship between Sciences and Education Lecturers’ Perceived Use of Mobile Technologies for Instruction - Taye Rasheed Rasheed Alani; Omotayo Olabo Obielodan; Amos Ochayi Onojah; Aderele Shadrack Omotayo; Adenike Aderogba Onojah; Ndaceko Joel Alasan (Media Komunikasi FPIPS, 2022)
Mobile technologies enable both education and science lecturers to provide the educational materials to their students on mobile technologies. But many science and education lectures educators were likely not using mobile technology to its maximum potential. The objectives were to examine the relationship between science and education lecturers and the effect of specialisation in the use of mobile technologies for instruction. The study was a descriptive research of survey type. 160 respondents were randomly selected for this study from the faculty of science and education. Frequency, percentage, multiple regression, and ANOVA were used for the analysis. The findings established that a positive relationship exists between science and education lecturers in the use of mobile technologies for instruction. It was recommended that lecturers should be encouraged to explore different ways in which mobile technologies can be used in teaching and learning.